2018
DOI: 10.1128/msystems.00015-18
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pathogenicity-Associated Loci in Klebsiella pneumoniae from Hospitalized Patients

Abstract: Klebsiella pneumoniae is a common cause of infections in the health care setting. This work supports a paradigm for K. pneumoniae pathogenesis where the accessory genome, composed of genes present in some but not all isolates, influences whether a strain causes infection or asymptomatic colonization, after accounting for patient-level factors. Identification of patients at high risk of infection could allow interventions to prevent or rapidly treat K. pneumoniae infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
63
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 47 publications
3
63
0
1
Order By: Relevance
“…Klebsiella virulence is largely attributable to lipopolysaccharide (LPS), pili, a polysaccharide capsule, and siderophores, and these are present in virtually all pathogenic strains ( 2 ). Features specifically linked to hypervirulence include additional siderophores ( 2 , 24 ), tellurite resistance ( 25 , 26 ), and hypermucoviscosity (HMV) ( 2 , 27 , 28 ). Capsule is also linked to hypervirulence, as the majority of hvKp strains have type K1 or K2 ( 24 ), although hv-associated traits have been found in strains with other capsule types ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Klebsiella virulence is largely attributable to lipopolysaccharide (LPS), pili, a polysaccharide capsule, and siderophores, and these are present in virtually all pathogenic strains ( 2 ). Features specifically linked to hypervirulence include additional siderophores ( 2 , 24 ), tellurite resistance ( 25 , 26 ), and hypermucoviscosity (HMV) ( 2 , 27 , 28 ). Capsule is also linked to hypervirulence, as the majority of hvKp strains have type K1 or K2 ( 24 ), although hv-associated traits have been found in strains with other capsule types ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…We then hypothesized that ter may be required during gut colonization, which precedes infection 2,3 . Exposure to antibiotics was not associated with Kp colonization or subsequent infection in our intensive care unit patient population 1,18 , indicating that Kp must contend with the indigenous microbiota to colonize the gut and cause infection. Previous studies have shown that gut microbiota differs by mouse vendor and by the room within each vendor facility (referred to as "barrier") 19 and these differences can impact experimental output [20][21][22] .…”
mentioning
confidence: 86%
“…We previously reported a strong association between ter and Kp infection (pneumonia and bacteremia) in colonized patients, yet also found that terC is dispensable in a murine model of pneumonia 1 . To determine if ter is important for bloodstream infection, WT Kp and terC were competed in a peritoneal injection model of murine bacteremia.…”
mentioning
confidence: 89%
“…In recent years, the importance of this opportunistic pathogen has increased significantly due to an increase in virulence and resistance to antibiotic therapy [ 3 , 4 ]. K. pneumoniae strains were found to be heterogeneous in terms of virulence factors, and recent studies showed that some virulence factors are important for growth at specific tissue sites (lungs, urinary tract, liver, and blood) [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%